LOS PERSONAJES FABULOSOS DEL JARDÍN DE FL ORES CURIOSAS DE ANTONIO DE TORQUEMADA. - Martinez-Góngora, Mar (Hispanófila, 2008)
A literary criticism of the book "Jardín de flores curiosas" by Antonio de Torquemada is presented. The article focuses on how the author integrates fantasy into the lives of the characters of the book. It also discusses Torquemada's vision of a hermaphrodite in the novel and his attention to the topic of gender.